Binomial Theorem PDF
Document Details
Uploaded by Deleted User
Tags
Summary
This document explains the binomial theorem for positive integral indices. It details factorial notation, permutations, and combinations. Examples and problems with solutions are also included.
Full Transcript
Binomial Theorem Factorial notation The notation π! or βπ represents the product of first π natural numbers. We read this symbol as βπ factorialβ. Thus, π! = 1 Γ 2 Γ 3 Γ 4 Γ...Γ (π β 1) Γ π = π Γ (π β 1) Γ...Γ 3 Γ 2 Γ 1. Example : 1! = 1 2! = 1 Γ 2 = 2 3! = 1 Γ 2 Γ 3 = 6 4! = 1 Γ 2 Γ 3 Γ 4 = 24 5! =...
Binomial Theorem Factorial notation The notation π! or βπ represents the product of first π natural numbers. We read this symbol as βπ factorialβ. Thus, π! = 1 Γ 2 Γ 3 Γ 4 Γ...Γ (π β 1) Γ π = π Γ (π β 1) Γ...Γ 3 Γ 2 Γ 1. Example : 1! = 1 2! = 1 Γ 2 = 2 3! = 1 Γ 2 Γ 3 = 6 4! = 1 Γ 2 Γ 3 Γ 4 = 24 5! = 1 Γ 2 Γ 3 Γ 4 Γ 5 = 120 We define 0! = 1. Note that, π! = π Γ (π β 1) Γ...Γ 3 Γ 2 Γ 1 = π(π β 1)! π! = π(π β 1)! = π(π β 1)(π β 2)! [Provided (π β₯ 2)] π! = π(π β 1)! = π(π β 1)(π β 2)(π β 3)! [Provided (π β₯ 3)] We can write, 6! = 6 Γ 5! = 6 Γ 120 = 720 12! 12Γ11Γ10! 10!2! = 10!Γ2 = 6 Γ 11 = 66 Permutations A permutation is an arrangement in a definite order of a number of objects taken some or all at a time. The number of permutations of π different things taken π at a time, where repetition is not allowed, is denoted by πππ and is given by π! πππ = (πβπ)! , where 0 β€ π β€ π. Combinations The number of combinations of π different things taken π at a time, denoted by ππΆπ , is given by π! ππΆπ = π!(πβπ)! , where 0 β€ π β€ π. Example : 10! 10! 10 Γ 9 Γ 8 Γ 7 Γ 6! 10πΆ4 = = = = 210 4! (10 β 4)! 4! 6! 4 Γ 3 Γ 2 Γ 1 Γ 6! 10! 10! 10 Γ 9 Γ 8 Γ 7 Γ 6! 10πΆ6 = = = = 210 6! (10 β 6)! 6! 4! 6! Γ 4 Γ 3 Γ 2 Γ 1 6! 6! 6 Γ 5 Γ 4 Γ 3! 6π3 = = = = 120 (6 β 3)! 3! 3! π! π! ππΆ0 = = =1 (π 0! β 0)! 1 Γ π! π! π Γ (π β 1)! ππΆ1 = = =π 1! (π β 1)! 1 Γ (π β 1)! π! π(π β 1)(π β 2)! π(π β 1) ππΆ2 = = = 2! (π β 2)! 2! (π β 2)! 2! π! π(π β 1)(π β 2)(π β 3)! π(π β 1)(π β 2) ππΆ3 = = = 3! (π β 3)! 3! (π β 3)! 3! π! π(π β 1)(π β 2)(π β 3)(π β 4)! π(π β 1)(π β 2)(π β 3) ππΆ4 = = = 4! (π β 4)! 4! (π β 4)! 4! β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦ π! π(π β 1)(π β 2) β¦ [π β (π β 1)] π(π β 1)(π β 2) β¦ (π β π + 1) ππΆπ = = = π! (π β π)! π! π! β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦β¦. π! π! π! ππΆπ = = = =1 π! (π β π)! π! 0! π! Γ 1 Some Properties 1) πππ = π! ππΆπ 2) ππΆπ = ππΆπβπ 3) ππΆπ + ππΆπβ1 = π + 1πΆπ 4) ππΆπ = ππΆπ β π = π or π = π β π ππΆπ πβπ+1 5) ππΆπβ1 = π Binomial Theorem for Positive Integral Indices Let us have a look at the following identities done earlier: (π + π)0 = 1 , π + π β 0 (π + π)1 = π + π (π + π)2 = π 2 + 2ππ + π2 (π + π)3 = π 3 + 3π 2 π + 3ππ2 + π3 (π + π)4 = (π + π)3 (π + π) = π 4 + 4π 3 π + 6π 2 π2 + 4ππ3 + π4 In these expansions, we observe that (i) The total number of terms in the expansion is one more than the index. For example, in the expansion of (π + π)2 , number of terms is 3 whereas the index of (π + π)2 is 2. (ii) Powers of the first quantity βπ β go on decreasing by 1 whereas the powers of the second quantity βπβ increase by 1, in the successive terms. (iii) In each term of the expansion, the sum of the indices of π and π is the same and is equal to the index of (π + π). Binomial theorem for any positive integer π (π + π)π = ππΆ0 π π + ππΆ1 π πβ1 π + ππΆ2 π πβ2 π 2 + ππΆ3 π πβ3 π 3 + β― + ππΆπβ1 πππβ1 + ππΆπ ππ = π π + ππΆ1 π πβ1 π + ππΆ2 π πβ2 π2 + ππΆ3 π πβ3 π3 + β― + ππΆπβ1 ππ πβ1 + ππ Here, ππΆ0 , ππΆ1 , ππΆ2 , ππΆ3 , β¦ , ππΆπ are called binomial co-efficients in the expansion of (π + π)π. Observations (i) There are (π + 1) terms in the expansion of (π + π)π, i.e., one more than the index. (ii) In the successive terms of the expansion the index of βπβ goes on decreasing by unity. It is π in the first term, (πβ 1) in the second term, and so on ending with zero in the last term. At the same time the index of βπβ increases by unity, starting with zero in the first term, 1 in the second and so on ending with π in the last term. (iii) In the expansion of (π + π)π , the sum of the indices of βπβ and βπβ is π + 0 = π in the first term, (π β 1) + 1 = π in the second term and so on 0 + π = π in the last term. Thus, it can be seen that the sum of the indices of βπβ and βπβ is n in every term of the expansion. Some Special Cases In the expansion of (π + π)π, (i) Taking π = π₯ and π = βπ¦ , we obtain (π₯ β π¦)π = [π₯ + (βπ¦)]π = ππΆ0 π₯ π + ππΆ1 π₯ πβ1 (βπ¦) + ππΆ2 π₯ πβ2 (βπ¦)2 + ππΆ3 π₯ πβ3 (βπ¦)3 + β― + ππΆπ (βπ¦)π = ππΆ0 π₯ π β ππΆ1 π₯ πβ1 π¦ + ππΆ2 π₯ πβ2 π¦ 2 β ππΆ3 π₯ πβ3 π¦ 3 + β― + (β1)π ππΆπ π¦ π Thus, (π₯ β π¦)π = ππΆ0 π₯ π β ππΆ1 π₯ πβ1 π¦ + ππΆ2 π₯ πβ2 π¦ 2 β ππΆ3 π₯ πβ3 π¦ 3 + β― + (β1)π ππΆπ π¦ π (ii) Taking π = 1 and π = π₯ , we obtain (1 + π₯)π = ππΆ0 1π + ππΆ1 1πβ1 π₯ + ππΆ2 1πβ2 π₯ 2 + ππΆ3 1πβ3 π₯ 3 + β― + +ππΆπ π₯ π Thus, (1 + π₯)π = ππΆ0 + ππΆ1 π₯ + ππΆ2 π₯ 2 + ππΆ3 π₯ 3 + β― + ππΆπ π₯ π In particular, for π₯ = 1 ,we have 2π = ππΆ0 + ππΆ1 + ππΆ2 + ππΆ3 + β― + +ππΆπ Thus, the sum of the binomial co-efficients in the expansion of (π + π)π is 2π. (iii) Taking π = 1 and π = βπ₯ , we obtain (1 β π₯)π = ππΆ0 1π + ππΆ1 1πβ1 (βπ₯) + ππΆ2 1πβ2 (βπ₯)2 + ππΆ3 1πβ3 (βπ₯)3 + β― + ππΆπ (βπ₯)π Thus, (1 β π₯)π = ππΆ0 β ππΆ1 π₯ + ππΆ2 π₯ 2 β ππΆ3 π₯ 3 + β― + (β1)π ππΆπ π₯ π In particular, for π₯ = 1 ,we have 0 = ππΆ0 β ππΆ1 + ππΆ2 β ππΆ3 + β― + (β1)π ππΆπ π π Problem : Expand (ππ + ) , π β π. π Solution : By using binomial theorem, we have 3 4 3 3 2 3 3 3 4 (π₯ 2 + ) = 4πΆ0 (π₯ 2 )4 + 4πΆ1 (π₯ 2 )3 ( ) + 4πΆ2 (π₯ 2 )2 ( ) + 4πΆ3 (π₯ 2 ) ( ) + 4πΆ4 ( ) π₯ π₯ π₯ π₯ π₯ 8 6 3 4 9 2 27 81 = π₯ + 4. π₯. π₯ + 6. π₯. π₯ 2 + 4. π₯. π₯ 3 + π₯ 4 108 81 = π₯ 8 + 12π₯ 5 + 54π₯ 2 + π₯ + π₯4 Problem : Expand (π β ππ)π. Solution : By using binomial theorem, we have (π₯ β 2π¦)5 = 5πΆ0 π₯ 5 β 5πΆ1 π₯ 4 (2π¦) + 5πΆ2 π₯ 3 (2π¦)2 β 5πΆ3 π₯ 2 (2π¦)3 + 5πΆ4 π₯(2π¦)4 β 5πΆ5 (2π¦)5 = π₯ 5 β 10π₯ 4 π¦ + 40π₯ 3 π¦ 2 β 80π₯ 2 π¦ 3 + 80π₯π¦ 4 β 32π¦ 5 General Term In Binomial Expansion (π + π)π = ππΆ0 π π + ππΆ1 π πβ1 π + ππΆ2 π πβ2 π 2 + ππΆ3 π πβ3 π 3 + β― + ππΆπβ1 πππβ1 + ππΆπ ππ We observe that, the first term= π‘1 = ππΆ0 π π = ππΆ0 π π π0 the second term= π‘2 = ππΆ1 π πβ1 π the third term= π‘3 = ππΆ2 π πβ2 π 2 the fourth term= π‘4 = ππΆ3 π πβ3 π3 From the above, we can generalise that the (π + 1)π‘β term= π‘π+1 = ππΆπ π πβπ ππ Thus, we have π‘π+1 = ππΆπ ππβπ π π This is called the general term in the binomial expansion of (π + π)π. Problem : Find the number of terms in the expansion of (π + π)π , where π is a positive integer. Solution Since the index of (π + π) is π , so the number of terms in the expansion of (π + π)π is (π + 1). π Problem : Find the number of terms in the expansion of (π + ππ + πππ + ππ ). Solution Note that,(1 + 3π₯ + 3π₯ 2 + π₯ 3 )7 = [(1 + π₯)3 ]7 = (1 + π₯)21. Therefore, the number of terms in the expansion of (1 + 3π₯ + 3π₯ 2 + π₯ 3 )7 is (21 + 1) = 22. π π Problem : Find the number of terms in the expansion of (ππ β π + ππ ). Solution 6 1 6 1 2 1 12 Note that, (π₯ 2 β 2 + ) = [(π₯ β ) ] = (π₯ β ). π₯2 π₯ π₯ 1 6 Therefore, the number of terms in the expansion of (π₯ 2 β 2 + π₯ 2) is (12 + 1) = 13. Problem : Find the number of terms in the expansion of (π + π)π (π β π)π. Solution Note that, (π₯ + π¦)7 (π₯ β π¦)7 = [(π₯ + π¦)(π₯ β π¦)]7 = (π₯ 2 β π¦ 2 )7 Therefore, the number of terms in the expansion of (π₯ + π¦)7 (π₯ β π¦)7 is (7 + 1) = 8. Problem : Find the second term in the expansion of (ππ + ππ)π. Solution Second term= π‘2 = π‘1+1 = 5πΆ1 (2π₯)5β1 (3π¦)1 = 5. 24. π₯ 4. 3π¦ = 240π₯ 4 π¦. Problem : Find the fifth term in the expansion of (π + π)π. Solution 5! 5Γ4! Fifth term= π‘5 = π‘4+1 = 5πΆ4. 16β4. π₯ 4 = 4!1! π₯ 4 = 4!Γ1 π₯ 4 = 5π₯ 4. π π Problem : Find the sixth term in the expansion of (π β π). Solution 1 5 9! 1 9Γ8Γ7Γ6Γ5! 1 126 Sixth term= π‘6 = π‘5+1 = 9πΆ5 π₯ 9β5 (β ) = β. π₯4. =β. =β. π₯ 5!4! π₯5 5!Γ4Γ3Γ2Γ1 π₯ π₯ π ππ Problem : Find the term independent of π in the expansion of (π β π). Solution : By using binomial theorem, we have 1 10 1 1 2 1 3 1 4 10 1 10 (1 β ) = 10πΆ0 β 10πΆ1. + 10πΆ2. ( ) β 10πΆ3. ( ) + 10πΆ4. ( ) β β― + (β1). 10πΆ10. ( ) π₯ π₯ π₯ π₯ π₯ π₯ st st From the above expansion, it is clear that 1 term is independent of π₯ and the 1 term is 10πΆ0 = 1. π ππ Problem : Find the term independent of π in the expansion of (π β π). Solution : 1 10 Let (π + 1)π‘β term be independent of π₯ in the expansion of (π₯ β π₯). 1 π Now, π‘π+1 = 10πΆπ (π₯)10βπ (β π₯) 1 = (β1)π 10πΆπ π₯10βπ. π₯ π = (β1)π 10πΆπ π₯10β2π Since π‘π+1 is independent of π₯, so index of π₯ is zero. β΄ 10 β 2π = 0 β 2π = 10 β π = 5. Hence (5 + 1)π‘β π. π. , 6th term is independent of π₯ and is given by π‘6 = π‘5+1 = (β1)5 10πΆ5 10! =β 5! 5! 10.9.8.7.6.5! =β 5.4.3.2.1.5! = β252 π ππ Problem : Find the term independent of π in the expansion of (π + π). Solution : 1 10 Let (π + 1)π‘β term be independent of π₯ in the expansion of (π₯ + π₯). 1 π Now, π‘π+1 = 10πΆπ (π₯)10βπ (π₯) 1 = 10πΆπ π₯10βπ. π₯ π = 10πΆπ π₯10β2π Since π‘π+1 is independent of π₯, so index of π₯ is zero. β΄ 10 β 2π = 0 β 2π = 10 β π = 5. Hence (5 + 1)π‘β , π. π. , 6th term is independent of π₯ and is given by π‘6 = π‘5+1 = 10πΆ5 10! = 5! 5! 10.9.8.7.6.5! = 5.4.3.2.1.5! = 252 π ππ Problem : Find the term independent of π in the expansion of (πππ β ππ). Solution : 1 12 Let (π + 1)π‘β term be independent of π₯ in the expansion of (9π₯ 2 β 3π₯). 1 π Now, π‘π+1 = 12πΆπ (9π₯ 2 )12βπ (β 3π₯) 1 = (β1)π 12πΆπ 912βπ. π₯ 24β2π. 3π π₯ π 1 = (β1)π 12πΆπ 912βπ. π₯ 24β3π. π 3 Since π‘π+1 is independent of π₯, so index of π₯ is zero. β΄ 24 β 3π = 0 β 3π = 24 β π = 8. Hence (8 + 1)π‘β , π. π. , 9th term is independent of π₯ and is given by 1 π‘9 = π‘8+1 = (β1)8 12πΆ8 912β8. 38 12! 912β8 = Γ 8 8! 4! 3 12 Γ 11 Γ 10 Γ 9 Γ 8! 94 = Γ 8 8! Γ 4 Γ 3 Γ 2 Γ 1 3 38 = 11 Γ 5 Γ 9 Γ 8 3 = 495 ππ βπ Problem : If the π independent term in the expansion of (βπ β ππ ) π’π¬ πππ , then find the value of π. Solution : 10 βπ Let (π + 1)π‘β term be independent of π₯ in the expansion of (βπ₯ β π₯ 2 ). 10βπ π βπ Now, π‘π+1 = 10πΆπ (βπ₯) (β π₯2 ) 10βπ π (βπ) = (β1)π 10πΆπ. π₯ 2. π₯ 2π π 10βπ β2π = (β1)π 10πΆπ. π2. π₯ 2 π 10β5π = (β1)π 10πΆπ. π2. π₯ 2 Since π‘π+1 is independent of π₯,so index of π₯ is zero. 10β5π β΄ 2 = 0 β 10 β 5π = 0 β 5π = 10 β π = 2. Hence (2 + 1)rd , π. π. , 3rd term is independent of π₯ and is given by π π‘3 = π‘2+1 = (β1)π 10πΆπ. π2 2 = (β1)2 10πΆ2. π2 10! = 2!8! π 10.9.8! = 2.8! π = 45π By given condition, 45π = 450 β π = 10 Problem : Find the co-efficient of ππ in the expansion of (π + ππ)ππ. Solution By using binomial theorem, we have (1 + ππ₯)10 = 10πΆ0 + 10πΆ1 (ππ₯) + 10πΆ2 (ππ₯)2 + 10πΆ3 (ππ₯)3 + β― + 10πΆ10 (ππ₯)10 = 1 + 10πΆ1 (ππ₯) + 10πΆ2 π 2 π₯ 2 + 10πΆ3 π 3 π₯ 3 + β― + π10 π₯10 So, the co-efficient of π₯ 2 in the expansion of (1 + ππ₯)10 is 10πΆ2 π 2 10! = 2!8! π 2 10.9.8! 2 = π 2.8! = 45π 2. π π ππ Problem : Find the co-efficient of ππ in the expansion of (π β π). Solution : By using binomial theorem, we have 1 10 1 1 2 1 3 1 10 (1 β ) = 10πΆ0 β 10πΆ1 ( ) + 10πΆ2 ( ) β 10πΆ3 ( ) + β― + 10πΆ10 ( ) π₯ π₯ π₯ π₯ π₯ 1 1 10 10! 10.9.8! So, the co-efficient of π₯ 2 in the expansion of (1 β π₯) is 10πΆ2 = 2!8! = 2.8! = 45. π ππ Problem : Find the co-efficient of πβπ in the expansion of (π β π ). Solution : By using binomial theorem, we have 1 10 1 1 2 1 3 1 10 (1 β ) = 10πΆ0 β 10πΆ1 ( ) + 10πΆ2 ( ) β 10πΆ3 ( ) + β― + 10πΆ10 ( ) π₯ π₯ π₯ π₯ π₯ 1 10 10! 10.9.8.7! So, the co-efficient of π₯ β3 in the expansion of (1 β π₯) is β10πΆ3 = β 3!7! = β 6.7! = β120. ππ Problem : Find the co-efficient of ππ in the expansion of (π + ππ + πππ + ππ ). Solution : Note that, (1 + 3π₯ + 3π₯ 2 + π₯ 3 )10 = [(1 + π₯)3 ]10 = (1 + π₯)30 = 30πΆ0 + 30πΆ1 π₯ + 30πΆ2 π₯ 2 + 30πΆ3 π₯ 3 + 30πΆ4 π₯ 4 + β― + 30πΆ30 π₯ 30 So, the co-efficient of π₯ 3 in the expansion of (1 + 3π₯ + 3π₯ 2 + π₯ 3 )10 is 30πΆ3. π π ππ Problem : Find the co-efficient of ππ in the expansion of (π β ππ ). Solution : By using binomial theorem, we have 1 10 1 1 2 1 3 1 10 (1 β 2 ) = 10πΆ0 β 10πΆ1 ( 2 ) + 10πΆ2 ( 2 ) β 10πΆ3 ( 2 ) + β― + 10πΆ10 ( 2 ) π₯ π₯ π₯ π₯ π₯ 1 1 10 10! 10.9.8.7! So, the co-efficient of π₯6 in the expansion of (1 β π₯ 2 ) is β10πΆ3 = β 3!7! = β 6.7! = β120. π ππ Problem : Find the co-efficient of sixth term in the expansion of (π β ππ). Solution : 1 5 Sixth term= π‘6 = π‘5+1 = 10πΆ5 π10β5 (β 2π) 1 = β10πΆ5. π 5. 25π 5 1 = β10πΆ5. 25 1 10 Thus, the co-efficient of sixth term in the expansion of (π β 2π) is 1 β10πΆ5. 25 10! = β 5!5! 10.9.8.7.6.5! 1 =β 5!5! Γ 32 10.9.8.7.6 1 = β 120 Γ 32 63 = β8 π π Problem : Find the co-efficient of πβπ in the expansion of (ππ β π). Solution : 7 8 Let (π + 1)π‘β term contain π₯ β2 in the expansion of (3π₯ β π₯). 7 π Now, π‘π+1 = 8πΆπ (3π₯)8βπ (β π₯) 7π = (β1)π 8πΆπ 38βπ. π₯ 8βπ. π₯ π = (β1)π 8πΆπ 38βπ. 7π. π₯ 8β2π Since π‘π+1 contains π₯ β2 , so index of π₯ is β2. β΄ 8 β 2π = β2 β 2π = 10 β π = 5. Hence (5 + 1)π‘β π. π. 6th term contains π₯ β2. Therefore, the co-efficient of π₯ β2 = (β1)π 8πΆπ 38βπ. 7π = (β1)5 8πΆ5 38β5. 75 = β8πΆ5. 33. 75 = β25412184 π ππ Problem : Find the co-efficient of π in the expansion of (ππ + π ). Solution : 5 π2 Let (π + 1)π‘β term contain π₯ in the expansion of (π₯ 2 + π₯ ). π π2 Now, π‘π+1 = 5πΆπ (π₯ 2 )5βπ ( π₯ ) π 2π = 5πΆπ. π₯10β2π. π₯π 2π 10β3π = 5πΆπ π π₯ Since π‘π+1 contains π₯, so index of π₯ is 1. β΄ 10 β 3π = 1 β 3π = 9 β π = 3. Hence (3 + 1)π‘β π. π. 4th term contains π₯. Therefore, the co-efficient of π₯ = 5πΆπ π 2π = 5πΆ3 π 6 5! 6 = π 3! 2! 5.4.3! 6 = π 3! Γ 2 = 10π 6 π ππ Problem : Find the co-efficient of πππ in the expansion of (ππ β ππ ). Solution : 1 10 Let (π + 1)π‘β term contain π₯10 in the expansion of (π₯ 2 β π₯ 3). 1 π Now, π‘π+1 = 10πΆπ (π₯ 2 )10βπ (β π₯ 3) 1 = (β1)π 10πΆπ. π₯ 20β2π. π₯ 3π = (β1)π 10πΆπ π₯ 20β5π Since π‘π+1 contains π₯10 , so index of π₯ is 10. β΄ 20 β 5π = 10 β 5π = 10 β π = 2. Hence (2 + 1)ππ , π. π. , 3rd term contains π₯10. Therefore, the co-efficient of π₯10 = (β1)π 10πΆπ = (β1)2 10πΆ2 10! = 2!8! 10.9.8! = 2.8! = 45 π ππ Problem : Find the co-efficient of π in the expansion of (π β πππ + πππ ) (π + π ). Solution : 1 10 (1 β 2π₯ 3 + 3π₯ 5 ) (1 + ) π₯ 1 1 1 1 1 1 = (1 β 2π₯ 3 + 3π₯ 5 ) (1 + 10πΆ1. + 10πΆ2. 2 + 10πΆ3. 3 + 10πΆ4. 4 + 10πΆ5. 5 + β― + 10 ) π₯ π₯ π₯ π₯ π₯ π₯ From the above multiplication, it is clear that the co-efficient of π₯ in the expansion of 1 10 (1 β 2π₯ 3 + 3π₯ 5 ) (1 + ) is π₯ β2 Γ 10πΆ2 + 3 Γ 10πΆ4 10! 10! = β2 Γ +3Γ 2! 8! 4! 6! 10 Γ 9 Γ 8! 10 Γ 9 Γ 8 Γ 7 Γ 6! = β2 Γ +3Γ 2 Γ 8! 4 Γ 3 Γ 2 Γ 1 Γ 6! = β90 + 630 = 540 π π Problem : If the 4th term in the expansion of (ππ + π) is independent of π, find the value of π. π Calculate π if the 4th term be π. Solution : 1 3 Here, π‘4 = π‘3+1 = ππΆ3 (ππ₯)πβ3 (π₯) 1 = ππΆ3. π πβ3. π₯ πβ3. π₯ 3 = ππΆ3. π πβ3. π₯ πβ6 Since π‘4 is independent of π₯, so index of π₯ is zero. β΄ π β 6 = 0 β π = 6. 5 If the 4th term be 2, then 5 π‘4 = 2 5 β ππΆ3. π πβ3. π₯ πβ6 = 2 5 β 6πΆ3. π 6β3. π₯ 6β6 = 2 6! 5 β π3 = 3! (6 β 3)! 2 6 Γ 5 Γ 4 Γ 3! 3 5 β π = 6 Γ 3! 2 6 Γ 5 Γ 4 Γ 3! 3 5 β π = 6 Γ 3! 2 1 β π3 = 8 1 βπ= 2 π π Problem : If the fifth term in the expansion of (ππ β π) is independent of π, find the value of π. Solution : 1 4 Here, π‘5 = π‘4+1 = ππΆ4 (π₯ 2 )πβ4 (β ) π₯ 1 = ππΆ4. π₯ 2πβ8. π₯ 4 = ππΆ4 π₯ 2πβ12 Since π‘5 is independent of π₯, so index of π₯ is zero. β΄ 2π β 12 = 0 β 2π = 12 β π = 6. π ππ Problem : If the third and fourth terms in the expansion of (ππ + π) are equal , then find the value of π. Solution : 1 2 1 Here , π‘3 = π‘2+1 = 10πΆ2 (2π₯)10β2 ( ) = 10πΆ2 (2π₯) 8. 8 82 1 3 1 and π‘4 = π‘3+1 = 10πΆ3 (2π₯)10β3 (8) = 10πΆ3 (2π₯) 7. 83 By the given condition, π‘3 = π‘4 1 1 β 10πΆ2 (2π₯)8. = 10πΆ3 (2π₯)7. 82 83 10! 10! 1 β. 2π₯ =. 2!8! 3!7! 8 10! 10! 1 β. 2π₯ =. 2! Γ 8 Γ 7! 3 Γ 2! Γ 7! 8 1 β 2π₯ = 3 1 βπ₯= 6 Problem : If in the expansion of (π + π)ππ the co-efficients of πππ term and (π + π)ππ term is in the ratio π βΆ π , then find the value of π. Solution : In the expansion of (1 + π₯)20 π‘π = π‘(πβ1)+1 = 20πΆπβ1 π₯ πβ1 π‘π+1 = 20πΆπ π₯ π By the given condition, π‘π 1 π‘π+1 =2 20πΆπβ1 1 β = 20πΆπ 2 20πΆπ β 20 =2 πΆπβ1 20βπ+1 ππΆπ πβπ+1 β =2 [β΅ = ] π ππΆπβ1 π β 20 β π + 1 = 2π β 21 = 3π βπ=7 π ππ Problem : If the co-efficient of ππ in the expansion of (πππ + ππ) be equal to the co-efficient of π ππ πβπ in the expansion of (ππ β ) , then prove that ππ = π. πππ Solution : 1 11 Let (π + 1)π‘β term contain π₯ 7 in the expansion of (ππ₯ 2 + ππ₯). 1 π 1 1 Now, π‘π+1 = 11πΆπ (ππ₯ 2 )11βπ (ππ₯) = 11πΆπ. π11βπ. π₯ 22β2π. πππ₯ π = 11πΆπ. π11βπ. ππ. π₯ 22β3π β΄ 22 β 3π = 7 β 3π = 15 β π = 5 1 β΄ π‘6 = 11πΆ5. π 6. 5. π₯ 7 π 1 11 Again, let (π + 1)π‘β term contain π₯ β7 in the expansion of (ππ₯ β ππ₯ 2). 1 π Now, π‘π+1 = 11πΆπ (ππ₯)11βπ (β ππ₯ 2 ) 1 = (β1)π 11πΆπ. π11βπ. π₯11βπ. ππ π₯ 2π 1 11β3π = (β1)π 11πΆπ. π11βπ..π₯ ππ β΄ 11 β 3π = β7 β 3π = 18 β π = 6 1 1 1 β΄ π‘7 = (β1)6 11πΆ6. π 5. π6. π₯ β7 = 11πΆ6. π 5. π6. π₯ β7 = 11πΆ5. π 5. π6. π₯ β7 [β΅ ππΆπ = ππΆπβπ ] By given condition, 1 1 11πΆ5. π 6. π5 = 11πΆ5. π 5. π6 1 βπ= π β ππ = 1 Middle terms in the expansion of (π + π)π Regarding the middle term in the expansion of (π + π)π , we have (i) If π is even, then the number of terms in the expansion will be π + 1. Since π is even, so π + 1 π+1+1 π‘β π π‘β is odd. Therefore, the middle term is ( 2 ) ,i.e., ( 2 + 1) term. 8 π‘β For example, in the expansion of (π₯ + 2π¦)8 , the middle term is ( + 1) ,i.e., 5th term. 2 (ii) If π is odd, then π + 1 is even. So, there will be two middle terms in the expansion, namely, π+1 π‘β π+1 π‘β ( ) term and ( + 1) term. 2 2 7+1 π‘β For example, in the expansion of (2π₯ β π¦)7 , the middle terms are ( ) ,i.e., 4th term and 2 7+1 π‘β ( + 1) term, i.e., 5th term. 2 π.π.πβ¦(ππβπ) Problem : Prove that the middle term in the expansion of (π + π)ππ is π!. ππ. ππ , where π is a positive integer. Solution : 2π π‘β Since 2π is even, so the middle term in the expansion of (1 + π₯)2π is ( 2 + 1) , i.e., (π + 1)π‘β term which is given by π‘π+1 = 2ππΆπ (1)2πβπ π₯ π (2π)! π = π!π! π₯ 1.2.3.4β¦.(2πβ2)(2πβ1)2π π = π!π! π₯ [1.3.5β¦(2πβ1)][2.4.6β¦.(2πβ2)2π] π = π!π! π₯ π [1.3.5β¦(2πβ1)]2 [1.2.3β¦(πβ1)π] π = π!π! π₯ [1.3.5β¦(2πβ1)]π! π π = π!π! 2 π₯ 1.3.5β¦(2πβ1) π π = π! 2 π₯ π π Problem : Find the middle term in the expansion of (πππ β ). π Solution : 1 8 Here π = 8 which is even. So, there is only one middle term in the expansion of (2π₯ 2 β π₯) and it is 8 π‘β (2 + 1) , i.e., 5π‘β term which is given by 1 4 π‘5 = π‘4+1 = 8πΆ4 (2π₯ 2 )8β4 (β π₯) 8! 1 = 4!4! 24 π₯ 8. π₯ 4 8.7.6.5.4! = 24.4!. 16π₯ 4 = 1120π₯ 4 π π Problem : Find the middle term in the expansion of (ππ β ππ). Solution : 1 8 Here π = 8 which is even. So, there is only one middle term in the expansion of (ππ₯ β ) and it is ππ₯ 8 π‘β ( + 1) , i.e., 5π‘β term which is given by 2 1 4 π‘5 = π‘4+1 = 8πΆ4 (ππ₯)8β4 (β ππ₯) 8! 1 = 4!4! π 4 π₯ 4. π4 π₯ 4 8.7.6.5.4! = 24.4! = 70 π π Problem : Find the middle term in the expansion of (ππ + ππ). Solution : 1 6 Here π = 6 which is even. So, there is only one middle term in the expansion of (ππ₯ + ππ₯) and it is 6 π‘β (2 + 1) , i.e., 4π‘β term which is given by 1 3 π‘4 = π‘3+1 = 6πΆ3 (ππ₯)6β3 ( ) ππ₯ 6! 3 3 1 = π π₯. 3 3 3!3! π π₯ 6.5.4.3! = 6.3! = 20 π π Problem : Find the middle term in the expansion of (ππ β ππ). Solution : 1 8 Here π = 8 which is even. So, there is only one middle term in the expansion of (3π₯ β 2π₯) and it is 8 π‘β (2 + 1) , i.e., 5π‘β term which is given by 1 4 π‘5 = π‘4+1 = 8πΆ4 (3π₯)8β4 (β ) 2π₯ 8! 4 4 1 = 4!4! 3 π₯. 24π₯ 4 8.7.6.5.4! 81 = Γ 24.4! 16 35Γ81 = 8 2835 = 8 π π Problem : Find the middle term in the expansion of (ππ + ). ππ Solution : 1 8 Here π = 8 which is even. So, there is only one middle term in the expansion of (π₯ 2 + π₯ 2) and it is 8 π‘β (2 + 1) , i.e., 5π‘β term which is given by 1 4 π‘5 = π‘4+1 = 8πΆ4 (π₯ 2 )8β4 (π₯ 2) 8! 8 1 = π₯. 8 4!4! π₯ 8.7.6.5.4! = 24.4! = 70 Infinite Series If β1 < π₯ < 1 , π. π. , |π₯| < 1,then (i) (1 β π₯)β1 = 1 + π₯ + π₯2 + π₯3 + π₯4 + π₯5 + β― (ii) (1 + π₯)β1 = 1 β π₯ + π₯2 β π₯3 + π₯4 β π₯5 + β― (iii) (1 β π₯)β2 = 1 + 2π₯ + 3π₯ 2 + 4π₯ 3 + 5π₯ 4 + 6π₯ 5 + β― (iv) (1 + π₯)β2 = 1 β 2π₯ + 3π₯ 2 β 4π₯ 3 + 5π₯ 4 β 6π₯ 5 + β― π Problem : Find the values of π for which (π β ππ)βπ can be extended in a binomial series. Solution : 1 1 1 (1 β 2π₯)β2 can be extended in a binomial series if β1 < 2π₯ < 1 , i. e., if β < π₯ <. 2 2 Problem : If |π| < π, then prove that (π + π + ππ + ππ + β― )(π β π + ππ β ππ + β― ) = π + ππ + ππ + ππ + β―. Solution : We have, (1 + π₯ + π₯ 2 + π₯ 3 + β― )(1 β π₯ + π₯ 2 β π₯ 3 + β― ) = (1 β π₯)β1 (1 + π₯)β1 [β΅ |π₯| < 1 ] = [(1 β π₯)(1 + π₯)]β1 = (1 β π₯ 2 )β1 = 1 + π₯ 2 + (π₯ 2 )2 + (π₯ 2 )3 + β― [β΅ |π₯| < 1 β |π₯ 2 | < 1] = 1 + π₯2 + π₯4 + π₯6 + β― Problem If π = π + π + ππ + + β― (|π| < π) ππ§π π = π + π + ππ + β― (|π| < π), then prove that ππ π + ππ + ππ ππ + β― =. π+πβπ Solution : Given, π₯ = 1 + π + π 2 + + β― (|π| < 1) and π¦ = 1 + π + π2 + β― (|π| < 1) β π₯ = (1 β π)β1 β π¦ = (1 β π)β1 1 1 β π₯ = 1βπ β π¦ = 1βπ π₯π¦ Now, π₯+π¦β1 1 1. 1βπ 1βπ = 1 1 + 1βπ 1βπ β1 1 (1βπ)(1βπ) = 1βπ+1βπβ(1βπ)(1βπ) (1βπ)(1βπ) 1 = 2βπβπβ1+π+πβππ 1 = 1βππ = (1 β ππ)β1 = 1 + (ππ) + (ππ)2 + β― [β΅ |π| < 1 &|π| < 1 β |ππ| < 1] = 1 + ππ + π 2 π2 + β― Exponential Series If π₯ is a real number, then π₯ π₯2 π₯3 π₯4 ππ₯ = 1 + + + + +β― 1! 2! 3! 4! Logarithmic Series (i) If β1 < π₯ β€ 1, then π₯2 π₯3 π₯4 logπ (1 + π₯) = π₯ β + β + β― 2 3 4 (ii) If β1 β€ π₯ < 1, then π₯2 π₯3 π₯4 logπ (1 β π₯) = βπ₯ β β β β β― 2 3 4